Learn more about

Refine search

Results (displaying matches 1-50 of 574) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
3469.a.3469.1 3469.a \(y^2 + (x^3 + x + 1)y = x^5 - x^4 - 2x^3\) $\mathrm{USp}(4)$ 2
3571.a.3571.1 3571.a \(y^2 + (x^3 + x + 1)y = -2x^4 + x^2 - x\) $\mathrm{USp}(4)$ 2
4989.a.14967.1 4989.a \(y^2 + (x^3 + x + 1)y = x^5 - 2x^3 + x\) $\mathrm{USp}(4)$ 2
5170.b.10340.1 5170.b \(y^2 + (x^3 + x^2 + x)y = -2x^2 - x + 1\) $\mathrm{USp}(4)$ 2
5295.a.79425.1 5295.a \(y^2 + (x^3 + x^2 + 1)y = -x^3 + 3x + 2\) $\mathrm{USp}(4)$ 2
5331.a.15993.1 5331.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^3 + x^2 - x\) $\mathrm{USp}(4)$ 2
5547.b.16641.1 5547.b \(y^2 + y = x^6 - 3x^5 + x^4 + 3x^3 - x^2 - x\) $G_{3,3}$ 2
5769.b.17307.1 5769.b \(y^2 + (x^3 + x + 1)y = x^5 - 3x^3\) $\mathrm{USp}(4)$ 2
6201.a.241839.1 6201.a \(y^2 + (x^3 + 1)y = 2x^5 - 13x^3 + 21x^2 - 12x + 2\) $\mathrm{USp}(4)$ 2
6291.e.56619.1 6291.e \(y^2 + (x^3 + x + 1)y = 2x^4 - x^2 - x\) $\mathrm{USp}(4)$ 2
7004.a.28016.1 7004.a \(y^2 + y = x^6 - 4x^4 - 4x^3 + x\) $\mathrm{USp}(4)$ 2
7389.a.22167.1 7389.a \(y^2 + (x^3 + x^2 + x)y = -2x^4 + x^2 - 2x + 1\) $\mathrm{USp}(4)$ 2
8204.a.32816.1 8204.a \(y^2 + y = x^6 - 2x^3 + 2x^2 - x\) $\mathrm{USp}(4)$ 2
8212.a.32848.1 8212.a \(y^2 + (x^3 + x)y = 2x^3 - x^2 - 2x + 1\) $\mathrm{USp}(4)$ 2
8450.c.84500.1 8450.c \(y^2 + (x^3 + 1)y = -5x^4 + 10x^3 - 5x^2\) $G_{3,3}$ 2
8452.a.16904.1 8452.a \(y^2 + (x^3 + x + 1)y = x^5 - 2x^4 - 3x^3 + x^2 + x\) $\mathrm{USp}(4)$ 2
8588.a.34352.1 8588.a \(y^2 + (x^2 + 1)y = x^6 - x^4 - x^3 + x\) $\mathrm{USp}(4)$ 2
8649.a.77841.1 8649.a \(y^2 + (x^3 + x + 1)y = x^3 + x^2 - 2x\) $G_{3,3}$ 2
9188.a.18376.1 9188.a \(y^2 + (x^3 + x + 1)y = x^4 - 2x^2 - x\) $\mathrm{USp}(4)$ 2
9585.a.86265.1 9585.a \(y^2 + (x^3 + 1)y = -2x^4 + 3x^3 - 3x^2 + 2\) $\mathrm{USp}(4)$ 2
9771.a.29313.1 9771.a \(y^2 + (x^2 + x + 1)y = x^6 + x^3 - x^2 - x\) $\mathrm{USp}(4)$ 2
10005.b.450225.1 10005.b \(y^2 + (x^3 + x + 1)y = -2x^4 + 3x^2 + x + 2\) $\mathrm{USp}(4)$ 2
10996.a.43984.1 10996.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^4 - 2x\) $\mathrm{USp}(4)$ 2
11079.b.33237.1 11079.b \(y^2 + (x^3 + x + 1)y = 3x^5 + 5x^4 + 2x^3\) $\mathrm{USp}(4)$ 2
11529.a.726327.1 11529.a \(y^2 + (x^3 + x + 1)y = -3x^4 + 5x^2\) $\mathrm{USp}(4)$ 2
11751.b.105759.1 11751.b \(y^2 + (x^3 + x + 1)y = -2x^4 + 3x^2 - x\) $\mathrm{USp}(4)$ 2
11944.a.95552.1 11944.a \(y^2 + (x^3 + x)y = x^5 - 2x^3 - x^2 + x + 1\) $\mathrm{USp}(4)$ 2
12105.a.181575.1 12105.a \(y^2 + (x^3 + x + 1)y = -x^4 + 3x^2 + 2x\) $\mathrm{USp}(4)$ 2
12700.a.25400.1 12700.a \(y^2 + (x^3 + x + 1)y = x^5 - 3x^3 - x^2 + x\) $\mathrm{USp}(4)$ 2
13006.b.832384.1 13006.b \(y^2 + (x^3 + x)y = -2x^4 + 4x^2 - 3x + 1\) $\mathrm{USp}(4)$ 2
13016.a.104128.1 13016.a \(y^2 + (x^3 + x)y = x^3 - x^2 - x + 1\) $\mathrm{USp}(4)$ 2
14724.a.88344.1 14724.a \(y^2 + (x^3 + x + 1)y = -x^5 - x^4 + x^2 - x\) $\mathrm{USp}(4)$ 2
15256.a.122048.1 15256.a \(y^2 + (x + 1)y = x^6 - x^4 + 2x^2 + x\) $\mathrm{USp}(4)$ 2
16034.a.32068.1 16034.a \(y^2 + (x^3 + 1)y = x^5 + x^4 + x^3 + x^2 - x\) $\mathrm{USp}(4)$ 2
16180.a.161800.1 16180.a \(y^2 + (x^3 + x + 1)y = x^5 + 4x^4 - x^2\) $\mathrm{USp}(4)$ 2
16719.a.451413.1 16719.a \(y^2 + (x^3 + x + 1)y = -x^4 + 3x^2 - 2x\) $\mathrm{USp}(4)$ 2
16767.b.452709.1 16767.b \(y^2 + (x^3 + x^2 + 1)y = -x^2 - x + 2\) $\mathrm{USp}(4)$ 2
17364.a.937656.1 17364.a \(y^2 + (x^3 + x + 1)y = x^5 + 2x^4 - x^2 - 2x\) $\mathrm{USp}(4)$ 2
18080.c.723200.1 18080.c \(y^2 + xy = x^6 - 2x^5 + x^3 + x^2 - 2x + 1\) $\mathrm{USp}(4)$ 2
18252.a.328536.1 18252.a \(y^2 + (x^3 + x + 1)y = -x^4 + 2x^3 + 2x^2 - 3x\) $\mathrm{USp}(4)$ 2
18624.b.446976.1 18624.b \(y^2 + (x^3 + x)y = -x^4 + 4x^2 - 4x + 1\) $\mathrm{USp}(4)$ 2
19881.b.536787.1 19881.b \(y^2 + y = x^6 - 3x^5 + 2x^4 + x^3 - 2x^2 + x\) $G_{3,3}$ 2
20096.b.160768.1 20096.b \(y^2 + (x^2 + 1)y = x^6 - 2x^4 - x^3 + x^2 + x\) $\mathrm{USp}(4)$ 2
20172.b.968256.1 20172.b \(y^2 + (x^2 + x)y = x^6 - x^5 - 2x^4 + 4x^3 - 3x + 1\) $G_{3,3}$ 2
20532.b.123192.1 20532.b \(y^2 + (x^3 + x + 1)y = 2x^6 - 3x^4 - x\) $\mathrm{USp}(4)$ 2
22112.b.353792.1 22112.b \(y^2 + y = x^6 - 6x^4 - 9x^3 - 4x^2\) $\mathrm{USp}(4)$ 2
22131.a.199179.1 22131.a \(y^2 + (x^3 + x + 1)y = 2x^6 - 4x^4 + x^2 - x\) $\mathrm{USp}(4)$ 2
22556.a.721792.1 22556.a \(y^2 + (x^3 + 1)y = 3x^3 + 2x^2 - 2x\) $\mathrm{USp}(4)$ 2
23412.a.140472.1 23412.a \(y^2 + (x^3 + x + 1)y = 2x^4 + x^3 - 2x^2 - x\) $\mathrm{USp}(4)$ 2
24704.a.790528.1 24704.a \(y^2 + x^3y = 6x^3 + 14x^2 + 12x + 4\) $\mathrm{USp}(4)$ 2
Next

Download all search results for